Decolourisation of chemically different dyes by enzymes from spent compost of Pleurotus sajor-caju and their kinetics - Singh, A.D.; Sabaratnam, V.; Abdullah, N.; Annuar, Mohamad Suffian Mohamad; Ramachandran, K.B. (Academic Journals, 2010)
A total of eight dyes from the triphenylmethane, azo and polymeric/heterocyclic dye group were decolourized by enzyme cocktail extracted from five month old spent compost of Pleurotus sajor-caju with lignin peroxidase as the main enzyme. The percentage of decolourisation for tryphan blue, amido black, remazol brilliant blue R (RBBR) and bromophenol blue ranged between 80 - 90% after 4 h reaction. However, the percentage of decolourisation for crystal violet, methyl green and congo red was lower than the other dyes from the same dye group with only 60 - 65% after 12 h. Methylene blue exhibited the least decolourisation with only 43% after 24 h indicating that this dye is a poor substrate for the enzyme. The rate of decolourisation for crystal violet, tryphan blue, amido black, congo red and RBBR dyes by enzymes from spent mushroom compost (SMC) were also calculated. The rate of decolourisation for all the dyes was positively affected by the initial dye concentration, pH between 4.0 - 4.5 and temperature range of 30 - 35 C. The optimum concentration of veratryl alcohol as redox mediator was between 0 - 2 mM for all the dyes except for RBBR. The optimum veratryl alcohol concentration for RBBR was 4 mM. Based on the effect of hydrogen peroxide on the rate of decolourisation of each dye, the dyes could be divided into two groups. From the results of the present study, it could be concluded that the enzymes extracted from the spent compost of P. sajor-caju offers an economical advantage of obtaining industrially important enzymes, which have potential in the bioremediation of synthetic dyes. Furthermore, the utilization of spent compost for the extraction of enzymes can also offer a possible solution for the problem posed due to the disposal of large amounts of spent mushroom compost.